Reconstruction and Peace Building in the Balkans: The Brcko Experience - Farrand, Robert William (Rowman & Littlefield Publishers, 2011)
In the tense aftermath of the 1992–1995 Bosnian War, U.S. diplomat Bill Farrand was assigned the daunting task of implementing the Dayton Peace Accords in the ethnically divided Balkan territory of Brcko in Bosnia and Herzegovina. Serb, Muslim, and Croat political leaders alike had blocked agreement over Brcko’s political status, thus threatening first to derail U.S.-brokered peace talks and then to prevent peace from taking hold in the postconflict period. This compelling narrative pulls the reader intimately into the author’s world where, over three tumultuous years, he was given wide authority to restore travel across former ceasefire lines, return thousands to their destroyed and confiscated homes, conduct free and fair elections, and reestablish multiethnic government bodies—all in a climate of fear and obstruction. “If we can get it right in Brcko,” the U.S. State Department told him, “we have a chance of making the Dayton peace process work throughout Bosnia.” Indeed, the new Brcko District is a Balkan success story. Farrand highlights the complex challenges peace builders confront, especially the role of civilian leadership in a postconflict zone torn apart by ethnic cleansing. Analytic and prescriptive, the book explains in vivid detail the groundbreaking roles of arbitration and of civilian peace workers living among the people. His story is rich in lessons for all those studying or engaged in peace building abroad.